How facial expressions reveal acute pain in domestic animals with facial pain scales as a diagnostic tool - Mota-Rojas, Daniel; Whittaker, Alexandra L.; Coria-Avila, Genaro A.; Martínez-Burnes, Julio; Mora-Medina, Patricia; Domínguez-Oliva, Adriana; Hernández-Avalos, Ismael; Olmos-Hernández, Adriana; Verduzco-Mendoza, Antonio; Casas-Alvarado, Alejandro; Grandin, Temple (Frontiers in Veterinary Science, 2025)
The growing interest in managing and recognizing pain in animals has led to the search for more sensitive methods to evaluate it, especially because some species conceal any visible changes associated with pain or are not easily assessed. Research has shown that an animal's facial expression changes when exposed to painful stimuli. Thus, developing several pain scales (grimace scales) in species such as horses, cattle, pigs, sheep, donkeys, rabbits, rats, mice, and cats has helped to improve the study of pain in veterinary medicine. The possibility of using facial expression as an indicator of pain is due to the direct relationship between the activation of different regions of the Central Nervous System such as the somatosensory cortex, prefrontal cortex, amygdala, hippocampus, and hypothalamus, and their connections with the motor cortex to elicit motor responses including the movement of facial muscles. The present review aims to discuss the neurobiological association between acute pain and facial expressions in animals. It will analyze the importance of facial expression characterization and the use of grimace scales in farm, companion, and laboratory species.